1999
DOI: 10.1080/030919099294294
|View full text |Cite
|
Sign up to set email alerts
|

An electrical impedance index to distinguish between normal and cancerous tissues

Abstract: Bioimpedance measurements have previously shown that cancerous tissues in many cases have a higher characteristic frequency than normal tissues. This paper tries to find an index which is sensitive to variation in the characteristic frequency but is independent of the impedance value itself. Calculated indexes from several publications in most cases show values larger than one for cancerous tissues and less than one for normal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…Modulated electrohyperthermia (mEHT) is a non-invasive local technique using capacitive coupled 13.56-MHz radiofrequency for targeted destruction of tumor cells (Andocs et al 2009a) based on the elevated conductivity, permittivity, and current density in cancer compared to normal tissue (Andocs et al 2009b;Blad and Baldetorp 1996;Blad et al 1999;Fiorentini and Szasz 2006;Zou and Guo 2003). We have previously revealed that mEHT at <42°C can dominantly induce a caspase-independent programmed cell death in HT29 colorectal cancer xenografts as a result of cell stress synergistically induced by the electric field and heat (Andocs et al 2009a;Meggyeshazi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Modulated electrohyperthermia (mEHT) is a non-invasive local technique using capacitive coupled 13.56-MHz radiofrequency for targeted destruction of tumor cells (Andocs et al 2009a) based on the elevated conductivity, permittivity, and current density in cancer compared to normal tissue (Andocs et al 2009b;Blad and Baldetorp 1996;Blad et al 1999;Fiorentini and Szasz 2006;Zou and Guo 2003). We have previously revealed that mEHT at <42°C can dominantly induce a caspase-independent programmed cell death in HT29 colorectal cancer xenografts as a result of cell stress synergistically induced by the electric field and heat (Andocs et al 2009a;Meggyeshazi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been previously shown that the electrical properties of cancerous tissue differ from those of normal tissue. 4,9 Specifically within the prostate areas of prostate cancer had higher impedance than areas of normal tissue. 4 Distinguishing cancerous from normal tissue using the Smart Needle system may be beneficial for diagnostic and therapeutic management of renal malignancy and malignancy in other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the fact that an increased conductivity may be used to identify the presence of tumors [43,44], there are lots of limitations for BIA metric analysis due to the complication and variation in the biological system [45]. Their important review by author Damijan et al [19] discussed efficiently lots of problems in the biological concern.…”
Section: Physiological Parameters Affecting Bioelectrical Impedance Amentioning
confidence: 99%